Narrativas digitales de la COVID-19 en Twitter: de los datos a la interpretación - Alles Torrent, Susanna (2020)
The bilingual project Digital Narratives of COVID-19 brings together researchers, programmers, and stu- dents from the University of Miami and CONICET (Argentina). DHCovid aims to analyze and interpret Twitter data (in English and Spanish) on the SARS-CoV -2 global pandemic from the end of April 2020 to May 2021, through quantitative methods and tools used in the field of DH. This article explores the differ- ent methods and tools that the project has used, from basic search platforms and semi-automated text- mining to more complex and more or less supervised ones. The paper additionally discusses how this set of tweets was collected to study the narratives and emerging issues about the pandemic in South Florida and specific Spanish-speaking countries (Argentina, Mexico, Peru, Colombia, Ecuador, Spain). Furthermore, it presents the GitHub and Zenodo data repository as well as some of the tools developed by the project. Finally, work with data mining, frequency analysis of terms and concordances, and topic modeling will be exhibited.